Idempotent D -cross-sections of the finite inverse symmetric semigroup ISn - Pyekhtyeryev, V. (Algebra and Discrete Mathematics, 2008)
We prove that every finite poset can be embedded in some idempotent D-cross-section of the finite inverse symmetric semigroup ISn.